2022
DOI: 10.1136/jnis-2022-018996
|View full text |Cite
|
Sign up to set email alerts
|

A novel self-expanding shape memory polymer coil for intracranial aneurysm embolization: 1 year follow-up in Chile

Abstract: BackgroundAneurysm recurrence remains a challenge when coiling cerebral aneurysms. Development of next generation coils has focused on accelerating thrombus maturation and increasing coil packing density. Ultra low density shape memory polymer is a novel embolic material designed for this purpose. The polymer is crimped over a platinum–tungsten coil for catheter delivery and self-expands to a predefined volume on contact with blood.MethodsThis prospective study in humans evaluated aneurysms 5–16 mm (inclusive)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…[135] It was found that SMP coils were efficient and safe for the treatment of intracranial aneurysms over 12 months in human studies. [132] Kunkel et al [2] characterized aliphatic urethane-based SMP for determining efficiency as a new material in embolization. The time of shape recovery was lower than 11 s with SMP formulations, being low enough to change shape during the embolization procedure.…”
Section: Shape Memory Polymers (Smps)mentioning
confidence: 99%
See 4 more Smart Citations
“…[135] It was found that SMP coils were efficient and safe for the treatment of intracranial aneurysms over 12 months in human studies. [132] Kunkel et al [2] characterized aliphatic urethane-based SMP for determining efficiency as a new material in embolization. The time of shape recovery was lower than 11 s with SMP formulations, being low enough to change shape during the embolization procedure.…”
Section: Shape Memory Polymers (Smps)mentioning
confidence: 99%
“…Expanded form possesses great surface area and promotes the formation of thrombus throughout its structure. [132] J. Wang et al [138] developed a biocompatible and highly porous PU SMP material for the fabrication of endovascular devices in the treatment of complex intracranial aneurysms. These researchers claimed that porous PU SMP material and electrical resistance heating trigger mechanism can enhance long-term therapeutic outputs of endovascular intracranial aneurysm therapy.…”
Section: Figure 12mentioning
confidence: 99%
See 3 more Smart Citations